Desafio no repente: a poética da cantoria na contemporaneidade - Santos, Edmilson Ferreira dos (2017)
This study proposes to talk about the challenge in the cantoria de repente and brings the discussion to contemporaneity. It discusses how the activity of the repentistas has adapted to the new technological apparatuses and how this new reality modifies the professional posture of these artists and implements new strategies of performance on stage and behind the scenes. It shows how professional and amateur improvisers, through portable devices, reproduce, virtually, the challenges, maintaining as reference base the traditional festivals of repentistas. These same technological artifacts that expand the frontiers of exposure of artistic work become tools of control of their activities. Cantorias are usually recorded in audio and / or video and many of them happen with live broadcast, through radio, WhatsApp and related apps, which broaden the inspection looks for consecration of repentistas and inhibition of repetistas. This work is anchored in the study of social practices in order to understand the phenomena inherent in the performance of the repentistas in front of the active participation of the listeners of their poetic making in various production and diffusion contexts. Therefore, internal and external questions to the activity of the repentistas are discussed, considering the importance of the challenge, the interference of the technology, and the listener's performance in the contemporary format of the cantoria de repente.